PENGARUH MODEL PEMBELAJARAN BERDIFERENSIASI TERHADAP HASIL BELAJAR SISWA KELAS V SDN 31 PALEMBANG - Mutiara, Hartanti Sinta; Mega Kusuma Putri; Hetilaniar (STKIP Subang, 2026)
This research aims to determine the improvement in learning outcomes of class V students at SDN 31 Palembang before and after implementing differentiation learning strategies in view of science learning. This research design uses Quasi Experimental Design. Quasi Experimental Design where there is only one research group that is measured before and after treatment. The research design uses a one group pretest-posttest design, consisting of one predetermined group. The subjects in this research were 28 class V students at SDN 31 Palembang. The instruments used to measure student learning outcomes are pre-test and post-test scores. As a result of the research that has been carried out and the discussion, the researcher concludes that there is an influence of the differentiated learning model on the learning outcomes of class V science students. This is shown by testing the hypothesis using the paired sample t test. The t value obtained is 6.392 > 2.048, the t table value df=28 is significant. (2-tailed) of 0.000 means that Ha is accepted and Ho is rejected.